Prevalencia de enteroparásitos en niños inmunocomprometidos e inmunocompetentes - Chourio-Lozano G; Díaz I; Rivero-Rodríguez Z; Peña C; Cuenca E; Calchi M; Molero E (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2002)
Abstract: Objetive: Determine the enteroparasite prevalence in immuno-compromised and Immunocompetent children in Zulia State, Venezuela. Materials and methods: Fecal samples from 78 children of both sexes, between the ages of 2 months and 12 years were distributed in 4 groups and analyzed: Undernourished (20), Oncological (20), with HIV/AIDS infection (18) and a control group (20); the copro-parasitology test, Lugol, Nair and Kinyoun stains, Ritchie concentration technique and Arakaki technique (agar in plaque) were used. Results: 29 (37,2%) children had one or several kinds of enteroparasites distributed as follows: 7/20 (35,0%) for the Undernourished and Control groups respectively, 8/20 (40,0%) for Oncology and 7/18 (38,9%) for the children with HIV/AIDS infection. The ethary group represented by the children two years of age of younger had more parasites which also occurred in undernourished control children and children from 3 to 6 years old for the Oncology group and children from 7 to 12 years old for the children with HIV/AIDS infection. The prevalent parasites were: Ascaris lumbricoides (14,3%) and Blastocystis hominis (24,5%). Conclusions: The immuno-compromised condition of these children under study (Undernourishment, Cancer and HIV/AIDS) was not significant for entero-parasite presence. Monoparasitism was prevalent in Undernourished, Oncology and Control groups and the poly-parasitism was prevalent in children with HIV/AIDS infection. The results obtained in this study represent a contribution to the knowledge of enteroparasitosis in our region. Resumen: Objetivo: Determinar la prevalencia de enteroparásitos en niños inmunocomprometidos e inmunocompetentes del Estado Zulia, Venezuela. Materiales y métodos: Se analizó una muestra fecal de 78 niños de ambos sexos, en edades comprendidas entre 2 meses y 12 años, distribuidos en 4 grupos: Desnutridos (20), Oncología (20), con infección HIV/SIDA (18) y Control (20); practicándose examen coproparasitológico, coloraciones de lugol, Nair y Kinyoun, técnica de concentración de Ritchie y técnica de Arakaki (agar en placa). Resultados: 29 (37,2%) niños presentaron una o varias especies de enteroparásitos, distribuidos así: 7/20 (35,0%) en los grupos de Desnutridos y Control respectivamente, 8/20 (40,0%) en Oncología y 7/18 (38,9%) en los niños con infección HIV/SIDA. Los menores o iguales a 2 años fue el grupo etario más parasitado tanto en el grupo Desnutridos como en los Controles; en Oncología fueron los de3a6 años, y en los niños con infección HIV/SIDA los de 7 a 12 años. Los parásitos más prevalentes fueron: Ascaris lumbricoides (14,3%) y Blastocystis hominis (24,5%). Conclusiones: La condición de inmunocomprometidos de los niños bajo estudio (Desnutrición, Cáncer y HIV/SIDA) no fue determinante en la presencia de enteroparásitos. El monoparasitismo predominó en los grupos de Desnutridos, Oncología y Control, y el poliparasitismo en el grupo de niños con infección HIV/SIDA. Los resultados obteni- dos en el presente estudio, representan un aporte más al conocimiento de las enteroparasitosis en nuestra región.